Pars Plana Vitrectomy vs Combined Pars Plana Vitrectomy-Scleral Buckle for Primary Repair of Pediatrics Retinal Detachment - Al Taisan AA (Dove Medical Press, 2021)
Abdulaziz A Al Taisan,1,2 Abdulaziz A Alshamrani,1 Abdullah T AlZahrani,3 Abdulelah A Al-Abdullah1 1Vitreoretinal Division, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 2Surgery Department, College of Medicine, King Faisal University, Al-Ahsa, Saudi Arabia; 3Glaucoma Division, King Khaled Eye Specialist Hospital, Riyadh, Saudi ArabiaCorrespondence: Abdulelah A Al-AbdullahVitreoretinal Division, King Khalid Eye Specialist Hospital, P.O. Box 7191, Riyadh, 11462, Saudi ArabiaTel +966 114821234 Ext. 2655Email aaabdullah@kkesh.med.saPurpose: To evaluate the outcome of pars plana vitrectomy (PPV) and combined pars plana vitrectomy with scleral buckle (PPV-SB) in the primary pediatrics rhegmatogenous retinal detachment repair.Design: A retrospective cohort study.Methods: A retrospective study was conducted in patients under 18 years of age, who presented with rhegmatogenous retinal detachment at King Khaled Eye Specialist Hospital between January 2014 and October 2018. Primary measurable outcomes were single surgery success rate (SSSR) and rate of postoperative complications.Results: A total of 122 eyes of 117 patients were included in the study; 80 eyes in PPV group and 42 eyes in PPV-SB group. Mean follow-up period after surgery was 18.2 months ± 11 months. SSSR was 76.3% (n=61) and 66.7% (n=28) for PPV and PPV-SB, respectively. No statistically significant difference was found between the two methods of RRD repair in single surgery success rate with an OR of 1.3 (P=0.45). Complication rates were comparable in both groups in the last follow-up.Conclusion: In this series, PPV and PPV-SB have comparable results in regard to anatomical success and rate of postoperative complications. More complicated cases were selected to undergo PPV-SB upon surgeons’ preference.Keywords: retinal detachment, pediatrics, pars plana vitrectomy, scleral buckle